Transcriptomic Responses Induced in Muscle and Adipose Tissues of Growing Pigs by Intravenous Infusion of Sodium Butyrate - He Zhang; Erdu Ren; Rongying Xu; Yong Su (Biology, 2021)
Butyrate has a central function in the regulation of energy metabolism as a metabolite of bacterial fermentation. This study evaluated the effects of intravenous sodium butyrate (SB) administration on the transcriptome of muscle and adipose tissue of pigs. Twelve crossbred barrows (Duroc × Landrace × Large White) were fitted with a medical polyethylene cannula via the internal jugular vein and were daily infused with 10 mL SB (200 mmol/L) or the same volume of physiological saline. Muscle transcriptome showed 11 DEGs related to carbohydrate metabolism, 28 DEGs related to lipid metabolism, and 10 DEGs related to amino acid metabolism. Among these, carbohydrate catabolic process-related genes (PPP1R3B, PRPS2, ALDOC), fatty acid synthase (FASN), and lipolysis-related genes (PLIN1) were upregulated, while the carbohydrate biosynthetic process-related genes (PCK1) and most amino acid metabolism-related genes were downregulated. Adipose transcriptome showed 12 DEGs related to carbohydrate metabolism, 27 DEGs related to lipid metabolism, and 10 DEGs related to amino acid metabolism. Among these, carbohydrate metabolism-related genes (IGF1, LEP, SLC2A4) and lipolysis-related genes (LPL) were upregulated, while lipolysis-related genes (ANGPTL4) and most amino acid metabolism-related genes were downregulated. The results suggest that short-term intravenous SB infusion could modulate the muscle and adipose tissue metabolism at the transcriptional level by decreasing amino acid metabolism pathways. Additionally, intravenous SB increased the glucose catabolism in muscle tissue and decreased the glucose utilization in adipose tissue. Intravenous SB increased the fatty acid synthesis, decreased the lipolysis in muscle tissue, and increased the lipolysis in adipose tissue. This suggests that systemic butyrate may display discriminative metabolic regulation in different tissues of barrows.